2021
DOI: 10.1007/s10811-021-02387-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of seaweed extract on tomato plant growth, productivity and soil

Abstract: This study investigated the effects of seaweed extract (SWE) made from the brown algae Durvillaea potatorum and Ascophyllum nodosum on plants and soil. The application of SWE to soil growing tomato plants showed dual effects. SWE comprehensively improved tomato plant growth (flower clusters, flower number, fruit number, root length, root and shoot dry weight, SPAD) and increased plant productivity (yield and quality). Similarly, SWE application effected soil biology at the soil root zone by increasing total ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 50 publications
2
33
0
Order By: Relevance
“…Our use of a well characterised model plant system and then extension into a common horticultural species has proven to be a powerful approach for elucidating the molecular priming responses induced by a biostimulant. It is evident from a recent study [5] that a seaweed extract made from A. nodosum and D. potatorum enhanced S. lycopersicum growth and productivity; likewise, in our laboratory system we confirmed a strong positive effect of SWE on health and root growth (Supplementary Figure S4). Priming in our study has been found to be strongly correlated with the expression of key priming-related genes and production of the reactive-oxygen species, H 2 O 2 , across both priming phases.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our use of a well characterised model plant system and then extension into a common horticultural species has proven to be a powerful approach for elucidating the molecular priming responses induced by a biostimulant. It is evident from a recent study [5] that a seaweed extract made from A. nodosum and D. potatorum enhanced S. lycopersicum growth and productivity; likewise, in our laboratory system we confirmed a strong positive effect of SWE on health and root growth (Supplementary Figure S4). Priming in our study has been found to be strongly correlated with the expression of key priming-related genes and production of the reactive-oxygen species, H 2 O 2 , across both priming phases.…”
Section: Discussionsupporting
confidence: 88%
“…Extracts from a single macroalgae, such as Ascophyllum nodosum, can stimulate an increase in plant growth, and increase crop productivity [2][3][4]. Other extracts derived from two brown algal species, A. nodosum and Durvillaea potatorum, also stimulated tomato plant growth and productivity and improved soil health [5].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it is plausible that some dosage issues may have been at play, especially in the latter study, as either A. nodosum treatments via fertigation on open field and greenhouse-grown tomato plants and combined pre-transplant soak and foliar spray on both tomato and pepper plants recorded significantly higher fruit yields [54,86].…”
Section: Implication Of Biostimulant Substance Treatments On Nightshade Green Growth and Fruit Yieldmentioning
confidence: 82%
“…As such, SWEs pose some risks in discussing them as a single entity due to their wildly varied selection of species, the inherent variation of their constituents based on climate and season, and the plethora of extraction modes [11]. Further increasing variation is the inclusion of either multi-species products, such as in the case of 'TAM', a mixture of Ulva lactuca, Jania rubens, and Pterocladia capillacea extracts [54], or non-algal derived matter such as 'Amalgerol', a mixture of oils and Ascophyllum nodosum extracts [55]. In the aptly named paper 'Comparative Transcriptome Analysis of Two Ascophyllum nodosum extract biostimulants: Same Seaweed but Different', Goñi and collaborators [56] showed that two A. nodosum extraction methods yield wildly different commercial products, which, in turn, provide for significantly different results in both formulate composition and plant response.…”
Section: Seaweed Extractsmentioning
confidence: 99%
“…Rathinapriya et al (2020) reported that, in foxtail millet, the application of liquid seaweed extracts improved plant growth and yield attributes and enhanced soil quality. Hussain et al (2021) reported that the foliar application of seaweed extract in tomato had improved the soil microbial communities, available nitrogen, and soil health. Maneaand Abbas (2018) suggested that in Broccolithe foliar application of seaweed extract enhanced the cabbage quality and quantity.…”
mentioning
confidence: 99%